(untitled) (قضايا سياسية, 2024)
The form and nature of the existing party system in any country is the main determinant of the effectiveness of the main political parties in the country. Academically, party systems are classified into multi-party systems, two-party systems, and single-party systems. Although there are other classifications that expand the number of these systems, what was mentioned is considered the most common from an academic standpoint. Since 2003 until the present, Iraq has known a multi-party system stipulated in the effective Constitution of 2005, and codified in the Political Parties Law of 2015. It is natural for this party system to have positive and negative effects, especially since Iraq has known for decades a one-party system in the sense of He did not know a multi-party system for a period of time, and therefore, the transition he witnessed from a single-party system to a multi-party system carried with it positive and negative effects on the state and society. In this research, we will attempt to study the reasons for that transformation and its implications.